RENEWABLE ENERGY RESOURCES AS A RELIABLE AND SUSTAINABLE SOURCE FOR RURAL ELECTRIFICATION AND DEVELOPMENT IN TANZANIA: Challenges of Renewable Energy Private Sector’s Investments in Tanzania - John, Felix Elimesia (My University, 2015)
Energy and the services provides has become most needed aspect for basic human needs, human comforts as well as for enhancing human health, wealth, education and better lifestyle. Reliable, affordable and sustainable energy supply is essential for social and economic development. Tanzania is facing a vast challenge on energy supply because the existing energy supply sources are overwhelmed by the growing rate of energy demand. The energy demand has grown high due to population growth, economic activities, technological changes and Tanzanian’s desire of better lifestyle. The growing energy demand and irregularity in power supply, requires the government to find way to enhance energy investment interests especially from private sector to enter in energy generation and supply sector with focus on using renewable energy sources. Renewable Energy Small and Medium-Sized Enterprises (RE SMEs) are seen as vital to individual and social economic development. However, RE SMEs in Tanzania are unable to effectively start up and/or substantially grow quantitatively as well as qualitatively due to various reasons. The purpose of this study is to deepen the understanding of the factors that hinder investments in renewable energy resources in rural area in Tanzania, to uncover the causes and give suggestions on what the government should do for existing Renewable Energy SMEs to perform successfully and attract more investors. The study was carried out using a questionnaire survey as tool for data collection. Questionnaires were sent to selected individuals, and some government authorities and RE SME owner-managers whose sample was selected from Tanzania Renewable Energy Association (TAREA) database and from Ministry of Energy and Mineral in Tanzania (MEM). Both qualitative and quantitative data analysis approach were used to analyze the data from questionnaires to identify potential barriers to investment in energy sector in a Tanzania context. The empirical result shows that high cost (capital) of investment and innovation that rated to 78.3%, lack of appropriate source of finance or loans that ranked to 79.1%, infrastructures scantiness in rural area that counts 68.5% and lack of purchasing power due to low income in rural societies and graded at 67.4% were revealed (table 4 below) as important dynamic aspects of the problem. The study findings suggested that the government should provide investors with easy access to loans, business stimulus, incentives and carefully and wisely planned tax exemptions or reduction. Also reduction of unnecessary procedure (bureaucracy), improved transparency, improved infrastructures and with strengthened and assured country’s political stability the more investors will get attracted. It also suggested need of appropriate policies and strategies that support RE SMEs to perform successfully and be more efficient in their servicing proving efforts.
Keywords: RE SMEs Investments Challenges/Barriers; Small and Medium-Sized Enterprises; SMEs Importance; Energy Essentiality; Renewable Energy Resources.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|